The Oppressor in the Mirror. Issue 2 (2nd April 2016) - Ellis, Kevin
Abstract : Mae hyn yn fy stori. Dw i'n symud ym Mae Treaddur o Birmingham yn mis Chwefror 2014. This is essentially my story. I moved to Bae Trearddur on the edge of Anglesey from Bartley Green in Birmingham. Nothing could have prepared me in many ways for the culture shock that I was about and continue to experience. I am an Anglican priest. I have been through a number of highly creative programmes that have made me aware of race, gender and sexuality. I pride myself on being tolerant and open in the way that anyone trained through the Queen's Foundation in Birmingham should be. All of this was brought into sharp focus by the relocation to Wales.